TACHYCARDIA-INDUCED CARDIOMYOPATHY AS A POTENTIALLY REVERSIBLE CAUSE OF HEART FAILURE - Kovačević, Vladan (Medicinski podmladak, 2023)
Cardiac arrhythmias often coexist with heart failure and can be its cause or a consequence. Tachycardia-induced cardiomyopathy most often occurs as a consequence of persistent atrial tachyarrhythmias, such as atrial fibrillation and atrial flutter. Accelerated heart rate leads to systolic and diastolic dysfunction of the left ventricle with its consequent dilation together with changes at the neurohumoral and cellular level. Clinical presentation varies from asymptomatic tachycardia to the end-stage heart failure. Tachycardia-induced cardiomyopathy is an often unrecognized and potentially reversible cause of heart failure. The exact prevalence of tachycardiomyopathy is difficult to determine because the diagnosis is made retrospectively, based on echocardiographically confirmed recovery of the left ventricular function after adequate treatment of the arrhythmia. The most effective treatment is catheter ablation of the arrhythmia. Other treatments include electrical cardioversion, pharmacological rhythm and/or rate control, and pacemaker implantation with ablation of the atrioventricular node.